PTRHD1 (C2orf79) mutations lead to autosomal‐recessive intellectual disability and parkinsonism. Issue 2 (18th October 2016) - Khodadadi, Hamidreza; Azcona, Luis J.; Aghamollaii, Vajiheh; Omrani, Mir Davood; Garshasbi, Masoud; Taghavi, Shaghayegh; Tafakhori, Abbas; Shahidi, Gholam Ali; Jamshidi, Javad; Darvish, Hossein; Paisán‐Ruiz, Coro
ABSTRACT: Introduction: Atypical parkinsonism is a neurodegenerative disease that includes diverse neurological and psychiatric manifestations. Objectives: We aimed to identify the disease‐cauisng mutations in a consanguineous family featuring intellectual disability and parkinsonism. Methods: Full phenotypic characterization, followed by genome‐wide single‐nucleotide polymorphism genotyping and whole‐genome sequencing, was carried out in all available family members. Results: The chromosome, 2p23.3, was identified as the disease‐associated locus, and a homozygous PTRHD1 mutation (c.157C>T) was then established as the disease‐causing mutation. The pathogenicity of this PTRHD1 mutation was supported by its segregation with the disease status, its location in a functional domain of the encoding protein, as well as its absence in public databases and ethnicity‐matched control chromosomes. Conclusion: Given the role of 2p23 locus in patients with intellectual disability and the previously reported PTRHD1 mutation (c.155G>A) in patients with parkinsonism and cognitive dysfunction, we concluded that the PTRHD1 mutation identified in this study is likely to be responsible for the phenotypic features of the family under consideration. © 2016 International Parkinson and Movement Disorder Society.